Stan czystości wód w Polsce oraz potrzeba inwestycji związanych z ich ochroną - Płóciennik, Danuta (Wydział Prawa i Administracji UAM, 1974)
The acquisition of water which is the basic condition of human living and economy becomes a more and more up-to-date problem for all humanity. The situation is growing worse because of the fact that with the social-economic development the demand for water increases but the water resources decrease and the water contamination increases at a terrifying rate. The struggle for clean water can be observed in abolishing of the main sources of contamination and in an effective water economy in all branches of the national economy. The problem becomes particularly significant in the water deficient areas with unfavourable hydrologic-meteorologic conditions where it is necessary to transport water from long distances. The main source of water supply are first of all surface flow waters and they ought to be the subject of great care and protection because of their destination particularly for drinking purposes but meanwhile they are the basic sewage collectors and they show a high level of contamination. In our country only about 50% of sewages are purified because of the small number of purification plants as well as their inefficiency. The building of purification plants is an invest-consuming undertaking. The building of new industrial-municipal purification plants creates the necessity to invest considerable amounts of money on the factories producing prefabricated elements. Up to 1990 the cost of purification plants building will amount to more than 14 milions zloties from which the greatest part is expected for municipal economy, heavy-industry and forestry.